2020
DOI: 10.5897/ajmr2020.9323
|View full text |Cite
|
Sign up to set email alerts
|

Food hygiene knowledge, attitude and practices among hospital food handlers in Elmanagil City, Sudan

Abstract: Food borne diseases (FBDs) can occur due to the health status of the food handlers. The present study aimed to assess food hygiene knowledge, attitude and practices among hospital food handlers of ElManagil City, Sudan. A cross-sectional study was administered to evaluate knowledge, attitudes, and practices, in food hygiene among hospital food handlers through a questionnaire. The food handlers expressed a level of knowledge, attitude, and practice of 70.1, 63.81 and 74.40%, respectively. The food handlers lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…In addition, the female, as a mother, takes care of her children. 1 , 24 , 25 This is also clearly found in this study where mothers are the responsible body of preparing food, and since mothers have also other house work burdens, there could be gaps in following necessary precautions for keeping safety of food.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the female, as a mother, takes care of her children. 1 , 24 , 25 This is also clearly found in this study where mothers are the responsible body of preparing food, and since mothers have also other house work burdens, there could be gaps in following necessary precautions for keeping safety of food.…”
Section: Discussionsupporting
confidence: 53%
“…This study reported that workers had moderate knowledge (59.7%) and practice (50%), which is slightly lower than the findings of the current study [ 22 ]. The findings are in line with earlier research in Pakistan (60.0% knowledge and 58.0% practice) [ 7 ], Malaysia (61.7% knowledge and 53.2% practice) [ 37 ], Lebanon (59.2% knowledge and 83.2% practice) (although practice score was higher) [ 9 ], and lower than Sudan (70.1% knowledge and 74.4% practice) [ 38 ]. The discrepancies reported among studies may be ascribed to disparities in study design, study sites, cutoff thresholds, training, and the accessibility of information pertaining to food hygiene and safety.…”
Section: Discussionsupporting
confidence: 91%
“…A factual examination showed a critical correlation between training level and washing the utensils with sanitizers and wearing gloves while performing work. This examination inferred that food treatment in El Managil hospital expresses a medium knowledge level and an uplifting outlook (47). Food hygiene education is the most effective when messages are directed towards changing behavior, the consequences of which are closely related to foodborne diseases.…”
Section: Factors Contributing To the Transmission Of Foodborne Diseasesmentioning
confidence: 93%